Rapamycin rescues mitochondrial dysfunction in cells carrying the m.8344A > G mutation in the mitochondrial tRNALys - Mariantonietta Capristo; Valentina Del Dotto; Concetta Valentina Tropeano; Claudio Fiorini; Leonardo Caporali; Chiara La Morgia; Maria Lucia Valentino; Monica Montopoli; Valerio Carelli; Alessandra Maresca (Molecular Medicine, 2022)
Abstract Background Myoclonus, Epilepsy and Ragged-Red-Fibers (MERRF) is a mitochondrial encephalomyopathy due to heteroplasmic mutations in mitochondrial DNA (mtDNA) most frequently affecting the tRNA Lys gene at position m.8344A > G. Defective tRNALys severely impairs mitochondrial protein synthesis and respiratory chain when a high percentage of mutant heteroplasmy crosses the threshold for full-blown clinical phenotype. Therapy is currently limited to symptomatic management of myoclonic epilepsy, and supportive measures to counteract muscle weakness with co-factors/supplements. Methods We tested two therapeutic strategies to rescue mitochondrial function in cybrids and fibroblasts carrying different loads of the m.8344A > G mutation. The first strategy was aimed at inducing mitochondrial biogenesis directly, over-expressing the master regulator PGC-1α, or indirectly, through the treatment with nicotinic acid, a NAD+ precursor. The second was aimed at stimulating the removal of damaged mitochondria through prolonged rapamycin treatment. Results The first approach slightly increased mitochondrial protein expression and respiration in the wild type and intermediate-mutation load cells, but was ineffective in high-mutation load cell lines. This suggests that induction of mitochondrial biogenesis may not be sufficient to rescue mitochondrial dysfunction in MERRF cells with high-mutation load. The second approach, when administered chronically (4 weeks), induced a slight increase of mitochondrial respiration in fibroblasts with high-mutation load, and a significant improvement in fibroblasts with intermediate-mutation load, rescuing completely the bioenergetics defect. This effect was mediated by increased mitochondrial biogenesis, possibly related to the rapamycin-induced inhibition of the Mechanistic Target of Rapamycin Complex 1 (mTORC1) and the consequent activation of the Transcription Factor EB (TFEB). Conclusions Overall, our results point to rapamycin-based therapy as a promising therapeutic option for MERRF.